Association between family income to poverty ratio and HPV infection status among U.S. women aged 20 years and older: a study from NHANES 2003-2016 - Zhao, Yuan; Zhao, Jing; Xie, Ruijie; Zhang, Yu; Xu, Ya; Mao, Jing; Yan, Cheng; Sun, Yi (Frontiers in Oncology, 2023)
Background HPV infection is closely related to the occurrence of cervical cancer and has an important adverse effect on human life and health. This study used data from the NHANES 2003–2016 to investigate the relationship between PIR and HPV infection status among Americans aged 20 and older. Methods The data for this cross-sectional investigation came from the 2003–2016 National Health and Nutrition Examination Survey (NHANES), which included 9580 women who were 20 years of age or older. The linear and nonlinear correlations between PIR and the presence of HPV infection were investigated using multiple linear regression and smooth curve fitting. The stability of the relationship across groups was examined using subgroup analysis and interaction tests. Results There were 2232 impoverished homes and 2543 rich households among the 9580 adult participants aged 20 and above. PIR (ratio of income to poverty) was found to be significantly inversely related to the presence of HPV infection [0.91 (0.89, 0.94)] after adjusting for all other covariates, and the trend persisted even after categorizing PIR into high- and low-income groups (PIR>4 and PIR<1). In addition, significant negative relationships were discovered in subgroup analyses for women aged 25 to 59 [0.90 (0.88, 0.93)], non-Hispanic whites [0.80 (0.70, 0.92)], non-diabetics [0.91 (0.88, 0.94)], and those who had ever engaged in sex [0.91 (0.89, 0.94)]. Conclusions PIR was highly and negatively correlated with the presence of HPV infection in American women aged 20 and older. The results of this study are of great significance for preventing HPV infection and improving the accuracy of HPV screening.